Teknologi Deteksi Dini Banjir Daerah Aliran Sungai menggunakan Heltec Wifi LoRa 32 V2 - Amanda, Feby; Samsugi, Selamet; Styawati, Styawati; Alim, Syahirul (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
In Indonesia there are often natural disasters, one of which is flooding. Flooding is a natural disaster that is marked by the overflowing of river water irrigation channels in urban areas, one is the river Irrigation that exists at the Technokrat University of Indonesia. Therefore, the study aims to develop a flood early detection tool using LoRa (Long Range) technology to monitor potential flooding in Kalibalau, Indonesian Technocratic University, Bandar Lampung. The research method involves installing an ultrasonic sensor in the Kalibalau River and connecting it to the Heltec Wifi LoRa 32 V2 microcontroller. Test results show that the LoRa transmitter and receiver operate as planned. This tool does not require an internet connection because it uses the Heltec Wifi LoRa 32 V2. The status of the river is categorized into four: Safe, Alert 1, Alert 2, and Danger, with appropriate warnings. The test showed a delay of 5 seconds on the water height reading. At safe (water height 44 cm), the buzzer does not sound. At morning 1 (water altitude 82 cm), it sounds once with a 1 minute delay. The device has a communication capacity of up to 400 meters. Thus, the tool is effective in monitoring the Kalibalau river and giving early warning of potential floods. This research has contributed to the development of flood monitoring technology to increase public alertness and safety in flood-prone areas